Existence ad Urgency of Asbab Al-Nuzul in the Contextual Interpretation of the Perspective of Hermeneutics Double Movement - Dewi Malihatil Himayah; Suqiyah Musafa’ah (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to reveal the existence and urgency of asbab al-nuzul as a tool for contextual interpretation, especially the double movement hermeneutic perspective. Classical commentators really prioritize interpretation using asbab al-nuzul as a tool in finding the meaning of verses. Meanwhile, contextual interpretation in the contemporary era is considered to exclude the tools of asbab al-nuzul which are usually used by classical commentators, moreover, linguistic interpretation considers that asbab al-nuzul is not important, such as the Bintu Syati' linguistic paradigm. This type of research is qualitative with a library research approach using article or book sources related to asbab al-nuzul. The results of this research show that asbab al-nuzul still has its urgency in contextual interpretation such as in double movement hermeneutics, because in revealing the message contained in the verses of the Koran, Fazlur Rahman's double movement method is used. Rahman's first move was to examine the historical situation and conditions behind a verse revealed called asbab al-nuzul. So this research can refute the assumption that asbab al-nuzul no longer has urgency in contemporary-contextual interpretation.